Number of gulls and corvids on a refuse dump - Karlsson, Thomas (Ornis Svecica, 2003)
The present study presents results from counts of gulls and corvids once a week on a refuse dump just outside the city of Skövde in southwestern Sweden during 1992—1999. The most common gull was Herring Gull Larus argentatus, which visited the dump during the whole year. The most common corvid was Jackdaw Corvus monedula with a peak in late June and July. All species except Jackdaw and Raven Corvus corax were found in small numbers during August. High numbers of gulls and corvids were seen on the refuse dump during the winter months. After that the community stopped dumping food rests on the refuse dump in January 1999, Herring Gull, Jackdaw, Hooded Crow Corvus cornix, and Black-headed Gull Larus ridibundus decreased during the spring and summer 1999, however not significantly. In the same time the number of Magpies Pica pica, Great Black-backed Gulls Larus marinus and Ravens increased.